2022
DOI: 10.1371/journal.pone.0273452
|View full text |Cite
|
Sign up to set email alerts
|

A bidirectional Mendelian randomization study supports the causal effects of a high basal metabolic rate on colorectal cancer risk

Abstract: Purpose We conducted a bidirectional two-sample Mendelian randomization (MR) study to determine whether genetically predicted basal metabolic rate (BMR) was a causal risk factor for colorectal cancer (CRC) or whether a genetically predicted CRC risk can influence the BMR level (i.e., reverse causation). Methods We employed 1,040 genetic variants as proxies for BMR to obtain effect estimates on CRC risk. Another 58 CRC-associated variants were used to estimate effects on BMR levels. Stratified analysis by tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…The BMR plays a significant role in maintaining bodily functions. As such, an increase in the BMR can indicate metabolic or endocrine system disorders, and the BMR has been shown to be associated with many metabolic diseases, such as cancer and osteoporosis [ 28 , 29 ]. Diseases characterized by an immune response have also been associated with an increased BMR due to a bioenergy imbalance [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BMR plays a significant role in maintaining bodily functions. As such, an increase in the BMR can indicate metabolic or endocrine system disorders, and the BMR has been shown to be associated with many metabolic diseases, such as cancer and osteoporosis [ 28 , 29 ]. Diseases characterized by an immune response have also been associated with an increased BMR due to a bioenergy imbalance [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several biological mechanisms can explain the positive correlation between a high BMR and OA risk. Individuals with a high BMR require more cellular energy to meet their metabolic needs [ 29 ]. Mitochondria are the main source of cellular metabolism and the mitochondrial respiratory chain is a primary source of cellular reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…Third, among individuals of normal weight and those who are overweight, there is a positive link between BMR and proinflammatory status (30,31). Elevated BMR can contribute to the generation of inflammatory cytokines such as interleukin (IL)-6 and interferon (IFN)-γ through inducing ROS production (32). Moreover, alterations in metabolic pathways and hormonal imbalances associated with high BMR, such as insulin resistance and dyslipidemia, may also contribute to a proinflammatory state (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, palindromically incompatible SNPs and SNPs detected using the Steiger Filter were removed 45 . A schematic of the three hypotheses of our MR study is shown in Fig.…”
Section: Quality Control Of Snpsmentioning
confidence: 99%